Mechanolysis mechanisms of the fused aromatic rings of anthracite coal under shear stress. (1st October 2019) - Wang, Jin; Guo, Guang-Jun; Han, Yuzhen; Hou, Quanlin; Geng, Ming; Zhang, Zhengcai
Abstract: The fused aromatic rings (FARs) of coal are considered to be relatively stable during coalification. However, it is speculated that defects may form in FARs during the deformation of coals under tectonic stress. In order to investigate the possibly existed mechanolysis reactions of FARs, we performed molecular dynamics simulations with the reactive force field to study an anthracite coal model under shear stress. The results show that the FAR rupture reactions occur much more efficiently than expected. There are two important ways to initiate FAR rupture: attacked rupture and direct rupture. Among the mechanisms, two types of rearrangement reactions play crucial roles. The first type is intra-ring rearrangement where the FAR forms a three-membered ring and a five-membered ring before rupture. The second type is extra-ring rearrangement where the location of substituent group changes. Both rearrangement reactions determine which bond in the FAR preferentially breaks but in different manners, and then promote the subsequent reactions. Comparing to pyrolysis mechanism, mechanolysis mechanism follows completely different reaction pathways and result in different products. This research will aid in understanding the reaction mechanisms of coal mechanochemistry, and it opposes the traditional standpoint that the FARs of coal are relatively stable and very hard to be destroyed during coalification.